ANALISIS SIKAP ILMIAH DAN TANGGAPAN MAHASISWA TERHADAP PENERAPAN MODEL PEMBELAJARAN BERBASIS PRAKTIKUM - Sukaesih, Sri (Jurnal Penelitian Pendidikan, 2011)
The objective of this research is to know the scientific attitude and students responses toward the implementation of practicum based learning program. The method used was quasi experiment with Nonequivalent Control Group Design . This observations was held in general biology subject, science education department, Semarang State University academic year 2009/2010. The sample used was two classes, they are: experiment class (38 people) and control class (38 people). Data obtained in this research is the scientific attitude of student data and student responses to learning data. Test difference of two scientific attitude means between the two treatment groups using the z test. Student response data as supporting data were analyzed descriptively qualitatively. The data analysis showes the students scientific attitude of the experiment class have N Gain 0.13 and the control class has N- Gain 0.06. Scientific Attitudes trial classes differ significantly from the control class level of significance Î± = 0.05. Students generally responded positively toward learning. The students declare pleased with the learning since it improves interest of learning, understands the concept easly, furthermore develops hands on and minds on. The Conclusion is practicum-based learning provide a positive influence on students' scientific attitude.